A Research of Construction Mechanism of Vassal State’s City Group during Spring and Autumn Period Based on the Analyzation of Geographic Image – Take south region of Shandong as example - X. Gao (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
Spring and Autumn period, the vassal states began to carry out country defense construction actively, brought changes to building the ideological. At that time, the south region of Shandong, as an independent unit of geography, seldom affected by external factors, and had striking cultural characteristics. Vassal states there constructed their capital mainly to defense the neighboring countries and cope with small scale mergers war, not involving the nationwide military deployment. Therefore, the region reflect the construction thought changes during the Spring and Autumn Period, and consistent with the research purpose. Based on this judgment, the author analyzed each capital’s location and terrain feature by topographic map. In brief, the Spring and Autumn Period, feudal states acted of one's own free will, the relationship between cities contained the one within and between vassal states. Within vassal state relationships included economic support, entrenching each other and protecting the country together. Meanwhile, strategic defensing, scrambling for resources and geographical location comprised of the competition between vassal states. In the agrarian age, the political centers and agricultural areas were interdependent, giving priority to the development of political cities. Transformation of capitals’ space layout was actually the process of carving up farming plains, the powerful states occupy favorable geographical position, and the small countries would be encroached and annexed gradually.